Nitric oxide oxidation on warped nanographene (C80H30): a DFT study - Thantip Roongcharoen (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. The possible use of the recently synthesized warped nanographene C80H30 for NO oxidation by O2 molecule has been investigated using density functional theory. The reaction starts with the adsorption and dissociation of O2 molecule on the central pentagon of C80H30 with the activation energies of 24.2–26.6 kcal/mol depending on the active sites. Then, the dissociated O atoms readily oxidize NO to NO2 twice. The first NO oxidation occurs with barrierless, while the second NO oxidation requires a small energy barrier of 16.0 kcal/mol. The low activation energy barrier pathway indicates high catalytic activity of this nanographene for NO oxidation. Charge analysis reveals that such high catalytic activity of nanographene is attributed to the charge transfer from the saddle-shaped C80H30 to the dissociated O atoms which makes it reactive to NO molecule. Desorption of NO2 product, which is the rate-limiting step of NO oxidation in some catalysts, is easily occurred in this nanographene (less than 2 kcal/mol), indicating the prevention of catalyst poisoning. This study suggests that C80H30 nanographene is a promising catalyst for NO removal in ambient condition.